An enhanced phenomenological model to predict surface-based localised corrosion of magnesium alloys for medical use. (February 2023) - Quinn, Conall; Van Gaalen, Kerstin; McHugh, Peter E.; Kopp, Alexander; Vaughan, Ted J.
Abstract: This study developed an enhanced phenomenological model for the predictions of surface-based localised corrosion of magnesium alloys for use in medical applications. The modelling framework extended previous surface-based approaches by considering the role of β-phase components throughout the material volume to better predict spatial and temporal aspects of surface-based corrosion in magnesium alloys. This enhanced surface-based corrosion model offers many advantages as it (i) captures multi-directional pitting, (ii) captures various pit morphologies, (iii) eliminates mesh sizing effects, (iv) reduces computational cost through custom time controls (v) offers control of pit sizing and (vi) produces corrosion rates that are independent of pitting parameter values. The model was fully implemented in three dimensions within the finite element framework and shows excellent potential to enable robust predictions of the long-term performance of magnesium-based implants undergoing corrosion.